TECTONO-STRATIGRAPHY AND TECTONIC EVOLUTION OF NORTH BUTON AND MUNA ISLANDS, SOUTHEAST SULAWESI - Wicaksono, Satrio
Muna and Buton Island, lies between latitudes 3 ° 55 '00 "S - 5 ° 30' 00"S and longitudes 122 ° 15 '00 "E - 123 ° 25' 00"E. Stratigraphic history in Southeast Sulawesi and Buton Island can be compared to the northwestern part of Australian Continental Margin. In general, the stratigraphy around Muna and Buton Island can be divided into sequences of Pre-Cenozoic and Cenozoic, where sedimentation associated with precollision and post-collision sedimentation. In general, there are three stages of geological processes were identified, namely Pre-Separation, Separation-Continental drift, and Post-Collision. In the Pre-separation stage consists of three units tectonostratigraphy, the Pre-Rift unit is Permian (Doole Formation), Syn-Rift unit Early Triassic age (Winto Formation and Meluhu), Post-Rift unit Late Triassic to Early Jurassic. Next on stage was identified as a unit Continental Rift-Drift is identified as Post-Rift in Late Cretaceous - Middle Miocene (Formation Tobelo). Two units tektonostratigrafi identified at this stage of the PostCollision are Syn-orogenic (Tondo Formation and Sampolakosa) and Recent Uplift (Wapulaka Formation). Research areas are located between the microcontinent interaction that originated from Southeast Sulawesi. Buton and Muna geological history began in Permian. Tectonic conditions at Permian - Early Cretaceous growing is Extensional. Extensional deformation consists of rifting processes and the formation of normal faults that cause subsidence. Stop the outbreak of this microcontinent in the Late Cretaceous and Australia moved north to Sundaland. First collisions occurs between Southeast Sulawesi and West Sulawesi/ Sundaland. Sorong Fault which formed the Early Miocene to control the movement of Tukang Besi and Buton microcontinent. Collision between Buton and Southeast Sulawesi / Muna occurred in the Middle Miocene, and the next collsion occurred between Buton and Tukang Besi microcontinent.